Participação popular na administração pública: as audiências públicas - Silva, Alessandra Obara Soares da (2009)
Every administrative activity, nowadays, elapses from a procedure. Whenever the procedure demands as one of its phases the previous knowledge and the possibility of participation of the particular interested, there´ll be process. It´s a goal of the and realizes the Democratic State of Law, the participation of the interested person in decision process that can interferer in one´s sphere of individual or collective rights. Due to the complex contemporary society, with multiple goals that elapses from pluralism, the need of a quick and efficient decision is evident. And, to conquer the public interest it´s evident that the State as one, on it´s decision activity, must know better the reality about what is going to decide. This knowledge is easily reached with public participation on decision process. And, the public hearing is one of the new instruments that materialize direct public participation. New, because it´s legal establishment is a recent phenomenon and the importance of it´s study is demonstrated by the quick increase of it´s prevision, with few specific studies about this theme. Especially about the accomplishment of public hearing in the scope of the Executive, the studies are few and, in practice, there´s still some resistance due to the fear of blocking or delaying the administrative function. Fear that should give up due to the need of transparence and efficiency on public administration, that is the typical activity of Executive